Online patient feedback: a scoping review and stakeholder consultation to guide health policy - Boylan, A-M; Williams, V; Powell, J (SAGE Publications, 2019)
Objective: To provide a synthesis of the current evidence base of online patient feedback using a scoping review and a consultation of stakeholders in England, UK.